Jeffrey William Lewis. The Business of Martyrdom: A History of Suicide Bombing - Assaf Moghadam (Perspectives on Terrorism)
Annapolis, MD: Naval Institute Press, 2012. 346 pp.; ISBN: 97816110514. US $ 39.95 Review by Assaf Moghadam